Perkawinan Budaya Dan Agama Pada Budaya Molang Areh Masyarakat Pedalaman Kabupaten Sumenep Madura - Zaitur Rahem; Abrari (HUMANISTIKA : Jurnal Keislaman, 2019)
One of the great influences of the Madurese community is derived from its culture. The culture of the local community born from its familiarity is able to sow the heritage of scientific heritage that gives bright colors to generations afterwards. The culture of Molang Areh as a form of a series of events in the event of ʻaqiqah (salvation on the birth of a baby) in the midst of the Madurese community has created scientific colors for its reviewers. A culture that does not have a proposition in this holy book, turns out to be a loose bow through religious teachings. The occurrence of marriages of culture and religious teachings can indicate that culture born from the mother tongue of the people of the interior of Madura has never been in conflict with the teachings of the religion that is present among the people. Keywords; Culture, Religion and Molang Areh